Housing Prices, Unemployment Rates, Disadvantage, and Progress toward a Degree - Leslie S. Stratton (Institute of Labor Economics (IZA), 2017)
Rising unemployment and housing price appreciation are associated with increased college enrollment. Enrollment does not, however, guarantee completion. We use a discrete time, competing hazard function that accommodates individual-specific heterogeneity to assess the impact changing unemployment and housing prices have on progress toward a college degree in the United States for students interviewed for the 1996-2001 Beginning Post-Secondary Survey. The results indicate that rising unemployment rates have at best a modest effect on six year graduation rates. Both boys and girls are, however, more likely to not be enrolled and less likely to have graduated at the six-year mark when housing prices appreciate, and this effect is more pronounced for more disadvantaged youth.
Keywords: I21; I24; 330; higher education; graduation; housing prices; unemployment; disadvantage